THE IMPACT OF SELENIUM SUPPLEMENTATION ON THE MECHANISMS OF THE INFLAMMATORY PROCESS IN PATIENTS WITH ULCERATIVE COLITIS: A SYSTEMATIC REVIEW - Paweł Grzesikowski; Dominika Liszka; Jakub Kubiak; Paulina Klich; Kinga Bekier; Hanna Nowicka (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Ulcerative colitis (UC) is one of the subtypes of inflammatory bowel disease (IBD), alongside Crohn’s disease. UC is associated with an inflammatory process occurring in the mucosa and submucosa of the large intestine. Various factors interact in the pathogenesis, determining the development and progression of UC. These include genetic and environmental factors, as well as changes in the immune system. The role of oxidative stress is also emphasized. Serum selenium (Se) levels in patients with UC were lower than in healthy individuals. Furthermore, the level of this microelement was inversely correlated with disease activity. In this paper, we review the physiological roles of Se and its impact on the course of UC. Given the multifaceted role of this microelement in the human body, we primarily focus on the influence of Se as a dietary component on immune response mechanisms and inflammation.Materials and methods: A systematic literature search was conducted using the electronic databases, including PubMed and Google Scholar. Various combinations of the following keywords were used in the search „ulcerative colitis”, „selenium”, „oxidative stress” and „ulcerative colitis pathophysiology”. The search was limited to publications from the last 5 years. Those directly related to the topic under discussion were then selected.Conclusions: Studies confirm the beneficial effect of Se on the course of UC. They present the mechanisms underlying the anti-inflammatory action of Se, from molecular processes at the gene expression level to clinical evidence demonstrating improved quality of life. The effects of Se supplementation appear promising, but further research in this area in needed.